FOREIGN DEBT MANAGEMENT ANALYSIS AND IMPACT ON ECONOMIC GROWTH - Habiburrahman HABIBURRAHMAN (International Conference On Law, Business and Governance (ICon-LBG), 2016)
In an effort to achieve prosperity and welfare of the people needed a high economic growth, it is Necessary for development in all areas including physical infrastructure development such as Infrastructure and other development projects which are investments that pretty much need of funds, not to mention the financing needs of others as listed in the state budget, also necessary to balance the Balance of payments. Meanwhile if domestic savings are not enough to finance all the investment required And the source for financing the state budget is not sufficient, the balance of payments (balance of Payment) is not balanced then the foreign debt be an alternative to cover the shortage of development funds.